Modern Views on the Prevalence, Gender Specificity, and Etiological Factors of Temporomandibular Disorders - Makeyev , В. Ф.; Shybinska , М. В. (Actual Dentistry, 2024)
Relevance. Temporomandibular disorders (TMD) remain a significant challenge for dentists across various specialties when diagnosing and treating them. Thus, current data on TMD’s prevalence and potential etiological factors are crucial for the initial diagnosis. Objective. To systematize and review modern views on temporomandibular disorders’ prevalence, gender-specific characteristics, and etiological factors. Materials and Methods. From 2017 to 2024, scientific and medical information was searched and systematically analyzed, including studies by foreign and Ukrainian researchers published in English and Ukrainian. During the literature analysis, three more recent publications were added, whose information was deemed relevant to the present. Results of the Study. It was determined that temporomandibular disorders remain relevant in identifying their etiological factors. The prevalence of TMD remains high, with significant gender-specific characteristics showing an increased incidence of TMD in women. Conclusions. Due to the relatively high prevalence of temporomandibular disorders, it is necessary to emphasize the importance of timely diagnosis of this pathology for dentists.